Dampak tax avoidence terhadap harga saham dengan corporate governance dan ukuran perusahaan sebagai variabel moderating - Yunita Valentina Kusufiyah; Dina Anggraini (JURNAL PUNDI, 2018)
The main purpose of a company that has go public is to generate profits in order to increase the prosperity of shareholders through increasing the value of the company. One of the management efforts to increase the value of the company is to reduce tax expense. Tax expense can be optimized through tax planning action. One of tax planning that does not violate the law one of them is by tax avoidance. Tax planning can be applied if Good Corporate Governance is done by management. This research aims to examine the effect of tax avoidence on the stock price of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research  aims to prove whether Corporate Governance and company size can moderate the effect of Tax Avoidance on the stock price of manufacturing companies listed on IDX. The research methodology used in this research is regression analysis that is linear regression analysis. The findings of this study that tax avoidence has an influence on stock prices. The management of the tax expense gets the attention of shareholders so as to raise the stock price.